THE USE OF VIDEO AS MEDIA IN TEACHING WRITING DESCRIPTIVE TEXT - Guswar Dwifadjrin; Mundriyah Pamungkas (IKIP Siliwangi, 2020)
Writing is one of the skills which must be mustered in learning English. However, many students het difficulties in learning writing. The objectives of the research entitled “ The used of video as media in teaching writing descriptive text” were to found out: 1) the implementation of the scenario in teaching English writing descriptive texts in seventh grade using video as media. 2) Students responses in learning descriptive text using video as media. In conducting this research, it was used a descriptive qualitative research design to describe the result of the research. The subject of the research was grade VII of junior high school in Padalarang, consit 20 students. The results of this study indicated that the implementation in teaching is done according to the scenario which was prepared by the researchers. The responses of the students based on the questionnaires showed that teaching learning proses using video was effective. Students had high enthusiasm, they did not feel monotonous, and they were motivated. From the result of assessment, most of the students had difficulties in writing English because they had poor grammar, lack of vocabulary, and poor understanding of mechanics in writing. In addition, the students had less experience because they were not accustomed to using English in writing. After learning using video as media, the student could overcome their difficulties eventhough there was few students that not understand grammar use, vocabulary, and mechanics in the final project. Keywords: Wring skill, Descriptive Text, Video